2010
DOI: 10.1179/107735210800546164
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Demographic Patterns of Non-Hodgkin's Lymphoma Incidence in Pennsylvania

Abstract: Objective Our study analyzed temporal and demographic patterns of non-Hodgkin’s lymphoma (NHL) incidence in Pennsylvania and compared Pennsylvania time trends with national trends. Methods Joinpoint and age-period-cohort analyses summarized sex- and race-specific NHL incidence time trends between 1985 and 2004. Ecologic analysis identified demographic factors associated with age-adjusted county-specific NHL incidence. Results NHL incidence in Pennsylvania increased annually 1.6% and 2.5% in white and black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…At the time of data analysis, HIV status at diagnosis was not available, leading to uncontrolled confounding of the association between DLBCL and CLL incidence rates and urban-rural status. However, we do not believe that differences in HIV prevalence would explain our results, given prior evidence that NHL incidence rates may be associated with degree of urbanization that is not attributed to HIV/AIDS prevalence alone [45,49]. Additionally, information on environmental and occupational exposures was not available and, while we hypothesize that the urban-rural incidence rate patterns observed in our study may be attributable to differential environmental exposures, additional research is needed to quantify exposures to suspected lymphomagens.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…At the time of data analysis, HIV status at diagnosis was not available, leading to uncontrolled confounding of the association between DLBCL and CLL incidence rates and urban-rural status. However, we do not believe that differences in HIV prevalence would explain our results, given prior evidence that NHL incidence rates may be associated with degree of urbanization that is not attributed to HIV/AIDS prevalence alone [45,49]. Additionally, information on environmental and occupational exposures was not available and, while we hypothesize that the urban-rural incidence rate patterns observed in our study may be attributable to differential environmental exposures, additional research is needed to quantify exposures to suspected lymphomagens.…”
Section: Discussionmentioning
confidence: 69%
“…The highest incidence was among non-Hispanic Blacks (49.6 per 100,000), followed by Hispanics (23.7 per 100,000) and non-Hispanic Whites (5.6 per 100,000). A study of NHL incidence rates in Pennsylvania, however, found increased NHL incidence rates with urbanization even after adjusting for county-level AIDS incidence, suggesting urban status may be independently associated with NHL risk [45]. Furthermore, while DLBCL is considered an AIDS-related lymphoma, FL and CLL have not consistently been attributed to HIV infection [46].…”
Section: Discussionmentioning
confidence: 99%